Engaging Scientific Diasporas in STEAM Education: The Case of Science Clubs Colombia - Avendano-Uribe, Bryann E.; Lombana-Bermudez, Andres; Flórez, Laura V.; Chaparro, Elisa; Hernandez-Morales, Adriana Carolina; Archbold, Jorge; Buitrago-Casas, Juan Camilo; Porras, Ana Maria (Frontiers in Research Metrics and Analytics, 2022)
Currently, there is limited insight on the role that scientific diasporas can play in STEAM education in Latin America. Here, we present the Science Clubs Colombia (Clubes de Ciencia Colombia-SCC) program, a pioneering STEAM capacity-building initiative led by volunteer scientists to engage youth and children from underserved communities in science. The program brings together researchers based in Colombia and abroad to lead intensive project-based learning workshops for young students in urban and rural areas. These projects focus on channeling the students' technical and cognitive scientific aptitudes to tackle challenges of both local and global relevance. The program provides high-quality STEAM education adapted to communities' needs and articulates long-lasting international collaborations using the mobility of the Colombian diaspora. The program's success is tangible via its sustained growth and adaptability. Since its first version in 2015, 722 volunteer scientists living abroad or in Colombia have collaborated to create 364 clubs with the participation of 9295 students. We describe elements of the SCC program that lead to a scalable and reproducible outcome to engage science diasporas in STEAM education. Additionally, we discuss the involvement of multiple stakeholders and the generation of international networks as potential science diplomacy outcomes. The SCC program strengthens the involvement of Latin American youth in science, demonstrates the potential of engaging scientific diasporas in science education, and enriches connections between the Global South and the Global North.